Implications of the serpentine phase transition on the behaviour of beryllium and lithium-boron of subducted ultramafic rocks - Vils, Flurin; Müntener, Othmar; Kalt, Angelika; Ludwig, Thomas (Geochimica et cosmochimica acta, 2011)
The Totalp-Platta-Malenco ophiolites in the Eastern Central Alps offer a unique opportunity to study the behaviour of Li, Be and B in ultramafic rocks in response to serpentinization and to progressive Alpine metamorphism. These units represent the remnants of a former ocean-continent transition that was intensely serpentinized during exposure on the Jurassic seafloor of the Ligurian Tethys. From north to the south, three isograd reactions (lizardite⇒antigorite+brucite;lizardite+talc⇒antigorite;lizardite+tremolite⇒antigorite+diopside) have been used to quantify the evolution of the light element content of metamorphic minerals. We determined the Li, Be and B concentrations in major silicate minerals from the ultramafic bodies of Totalp, Platta and Malenco by secondary ion mass spectrometry. Mantle minerals have Be concentrations (e.g. <0.001-0.009μg/g in olivine) similar to the metamorphic minerals that replace them (e.g. <0.001-0.016μg/g in serpentine). The mantle signature of Be is thus neither erased during seafloor alteration nor by progressive metamorphism from prehnite-pumpellyite to epidote-amphibolite facies. In contrast, the Li and B inventories of metamorphic minerals are related to the lizardite-to-antigorite transition. Both elements display higher concentrations in the low-temperature serpentine polymorph lizardite (max. 156μg/g Li, max. 318μg/g B) than in antigorite (max. 0.11μg/g Li, max. 12μg/g B). Calculated average B/Li ratios for lizardite (∼1395) and antigorite (∼115) indicate that Li fractionates from B during the lizardite-to-antigorite transition during prograde metamorphism in ultramafic rocks. In subduction zones, this signature is likely to be recorded in the B-rich nature of forearc fluids. Relative to oceanic mantle the Be content of mantle clinopyroxene is much higher, but similar to Be values from mantle xenoliths and subduction-related peridotite massifs. These data support previous hypothesis that the mantle rocks from the Eastern Central Alps have a subcontinental origin. We conclude that Be behaves conservatively during subduction metamorphism of ultramafic rocks, at least at low-temperature, and thus retains the fingerprint of ancient subduction-related igneous events in mantle peridotites.